2006
DOI: 10.1159/000093184
|View full text |Cite
|
Sign up to set email alerts
|

Regression Tree Approach to Studying Factors Influencing Acoustic Voice Analysis

Abstract: Multiple factors influence voice quality measurements (VQM) obtained during an acoustic voice assessment including: gender, intrasubject variability, microphone, environmental noise (type and level), data acquisition (DA) system, and analysis software. This study used regression trees to investigate the order and relative importance of these factors on VQM including interaction effects of the factors and how the outcome differs when the acoustic environment is controlled for noise. Twenty normophonic participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 19 publications
(29 reference statements)
1
29
0
4
Order By: Relevance
“…These results replicated or supported a number of studies that have demonstrated the robust and invariant nature of key frequency and timing-based measures (Mundt et al, 2007), and the sensitive character of supplementary acoustic parameters (Carding et al, 2004;Deliyski et al, 2006).…”
Section: Perturbationsupporting
confidence: 83%
See 1 more Smart Citation
“…These results replicated or supported a number of studies that have demonstrated the robust and invariant nature of key frequency and timing-based measures (Mundt et al, 2007), and the sensitive character of supplementary acoustic parameters (Carding et al, 2004;Deliyski et al, 2006).…”
Section: Perturbationsupporting
confidence: 83%
“…Deliyski and colleagues have conducted a series of comprehensive studies investigating the influence of data acquisition environments (Deliyski, Shaw, Evans, & Vesselinov, 2006), sampling rate (Deliyski et al, 2005a), and environmental noise (Deliyski, Evans, & Shaw, 2005). The authors have concluded that gender, intrasubject variability, microphone selection, environmental noise (type and level), data acquisition system, and analysis software all play a role in voice quality measurements.…”
mentioning
confidence: 99%
“…Espectrograma com traçado regular, intensidade fraca, estável, com ruído ausente, sub-harmônicos ausentes e harmônicos definidos até 3 kHz de normalidade diferem entre eles. Além disso, esses valores também variam conforme os instrumentos de gravação, ruído ambiental, gênero e idade do falante (14,15) o que mostra que a qualidade do equipamento utilizado no registro das vozes, o tipo de programa e as características anatomofuncionais da laringe podem influenciar nos resultados destas medidas a curto prazo.…”
Section: Discussionunclassified
“…Thus, individual hardware components such as microphones [15,16] and recording hardware [11,17] may be independent sources of error, but the fidelity of the system with all the components working in synergy will ultimately reveal the error in application.…”
Section: Hardware Configurationsmentioning
confidence: 99%
“…Adoption of alternative technologies in voice research has been slow, perhaps due to the requirement for high-quality recording devices needed for some types of analyses (e.g., measures of perturbation) [9,10,11,12]. Historically, only professional-grade data acquisition systems have been accepted as valid and reliable methods for collecting speech data [13].…”
mentioning
confidence: 99%